PENGARUH LATIHAN DRIBBLING SAMBIL MELINGKAR TERHADAP KETERAMPILAN DRIBBLING TIM BASKET PUTRA SMA NEGERI BERNAS BINSUS PROVINSI RIAU - Ridho Dwi Achwilya; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that the Men's Basketball Team of SMA NEGERI BERNAS BINSUS Riau Province in playing basketball while dribbling the ball is too easy for the opponent to grab, because the mastery of basic techniques is not fully maximized, such as dribbling. This study was conducted to determine whether there is an effect of dribbling training while in a circle on the dribbling ability of basketball games in the men's basketball team of SMA NEGERI BERNAS, RIAU PROVINCE. This type of research is a preetest posttest one group design. The sample in this study was the men's team of SMA NEGERI BERNAS, RIAU PROVINCE, totaling 10 people with purposive sampling technique. Based on the results of the research and data processing, there is an effect of dribbling training while in a circle on the dribbling skills of the SMA NEGERI BERNAS BINSUS basketball team, RIAU PROVINCE. These results are indicated by the research data as follows: the number of pretest data is 178 with an average value of 17.8 and the number of post-test data is 229 with an average value of 22.9. Then the analysis of the 'T' test resulted in Tcount of 10.13 and Ttable of 1.833. Means Tcount (10,13) > Ttable (2,015). It can be concluded that there is an effect of dribbling practice with dribbling practice while in a circle on the dribbling skills of the men's basketball team at SMAN BERNAS, RIAU PROVINCE.Key Words: Dribble, Dribble While In A Circle